PERHITUNGAN DAN TATA CARA PEMOTONGAN PPH PASAL 21 ATAS ANGGOTA POLRI PADA POLRES BARITO UTARA KALIMANTAN TENGAH - Winda Dewi Nurhanisa; Sustinah Limarjani (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2020)
The purpose of this study was to determine the calculation of PPh Article 21 and to know the procedures for withholding Income Tax Article 21 on the income of Polri members at the North Barito Police Station, Central Kalimantan. The results of this study indicate that: First, make a comparison between the calculation of PPh Article 21 of the North Barito Police, namely using the GPP application which is automatically calculated with manual calculations taught during lectures. The calculation of the North Barito Police is in accordance with the applicable laws and regulations. Second, the procedure for deductions at the North Barito Police, namely the Paying Officer makes monthly deductions by inputting the income of Polri members in the GPP application which will be deducted automatically. Then, the Paying Officer uses the SAS application to issue the relevant monthly salary SPM as BUN, then it is printed and sent to the KPPN. The payroll process is carried out until the SPPD is issued by the KPPN and will be forwarded to the BRI Bank account of each member.